Theoretical Foundations For Improving The Software And Methodological Support For Teaching Students The Subject Of Informatics In Primary Education And Its Teaching Methods - Xomidova Zohidjon Adhamovich (European International Journal of Pedagogics, 2026)
This article focuses on the theory that can strengthen both software tools and methodological techniques for teaching Informatics to primary education students. In addition, it identifies the current challenges in integrating the Informatics course at the primary education level and suggests better techniques to optimize the learning process. In particular, emphasis is put on optimizing educational software tools as they relate to meeting pedagogical needs, as well as effective teaching techniques for primary students. This will ensure guidelines to improve the learning process in Informatics among such students.